Edukasi Pemanfaatan Layanan BPJS Kesehatan pada Peserta BPJS di Klinik Pratama Arinda Medika - Lina Contesa; Rama Agustina (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Limited understanding among BPJS Health participants regarding their rights and obligations, service procedures, and the tiered referral system may lead to suboptimal utilization of healthcare services. This condition may result in misunderstandings in service use and affect the effectiveness of healthcare delivery. This community service program aimed to improve participants’ knowledge regarding the utilization of BPJS Health services at Arinda Medika Primary Clinic. The methods included pretest administration, health education sessions, interactive discussions, question-and-answer sessions, leaflet distribution, and posttest evaluation. The educational materials covered participants’ rights and obligations, service procedures at primary healthcare facilities, the tiered referral system, and the types of services covered by BPJS Health. The results demonstrated an improvement in participants’ knowledge after the educational intervention. Participants also showed a better understanding of healthcare service procedures and how to access healthcare services in accordance with existing regulations. Education on the utilization of BPJS Health services has the potential to become an effective promotive strategy to improve health literacy and optimize the use of primary healthcare services.